Konseling Realita Berbasis Choice Theory dan Model Wdep: Konsep dan Implikasinya dalam Dunia Pendidikan - Rochiyatin Rifai; Bakhrudin All Habsy (CV. Green Publisher Indonesia, 2026)
In the context of 21st-century education, the increasing problems of student behavior and mental health require an individual empowerment-based counseling approach such as Reality Counseling which emphasizes internal control and conscious choice to overcome academic failure and build students' positive identities. This article aims to explore in depth the Reality Therapy approach developed by William Glasser and its relevance in the context of modern education. As an approach focused on the present and personal responsibility, Reality Counseling offers a practical framework through Choice Theory. The method used in this paper is a narrative literature study synthesizing various primary and secondary sources, including material from the William Glasser Institute. Key findings suggest that human behavior is driven by five basic genetic needs: survival, love and belonging, power, freedom, and fun. Through the concept of Total Behavior and the WDEP (Wants, Direction, Evaluation, Planning) Model, counselors can guide students to evaluate the effectiveness of their own behavior and develop more constructive action plans. Implications for guidance and counseling (BK) practice in schools include strengthening teacher-student relationships, increasing responsibility for learning, and developing a success identity. This article concludes that the systematic implementation of Reality Counseling can create a school environment without failure (Schools Without Failure) that supports the psychological well-being and academic achievement of students